Formulation and Evaluation of Herbal Shampoo containing Red Dragon Fruit Peel Extract (Hylocereus polyrhizus (Hook.) Britton & Rose): toward A Potential Anti-Dandruff Application - Desti Kameliani; Sukmawati Sukmawati; Herliningsih Herliningsih; Cucu Suhartini (Journal of Food and Pharmaceutical Sciences, 2026)
Dandruff is a common scalp condition influenced by factors such as an oily scalp, hormones, and fungal infections. Red dragon fruit peel (Hylocereus polyrhizus) contains flavonoids with natural antimicrobial activity, making it a promising natural ingredient for scalp care. This study aimed to develop and evaluate herbal shampoo containing red dragon fruit peel extract. Four formulations were prepared with different concentrations of extract: F0 (base), F1 (6.25%), F2 (12.5%), and F3 (25%). Each was assessed for organoleptic properties, homogeneity, pH, viscosity, foam height, and foam stability. The stability test was evaluated using a cycling test. Data analysis with One-way ANOVA revealed that extract concentration significantly influenced pH and viscosity stability (p < 0.05). F1 showed optimal physical properties and complied with SNI 06-2692-1992 standards. These findings support the potential use of red dragon fruit peel extract in herbal shampoo formulations for future anti-dandruff applications.